Philippine mineral resources towards the horizon: A webinar series on mineral resources management - CESDR - De La Salle University, Manila (Animo Repository, 2021)
Center for Engineering and Sustainable Development Research Waste and Resource Management Unit cordially invited the Lasallian community (students, faculty and researchers) to attend the webinar series “Philippine Mineral Resources towards the HORIZON: A Webinar Series on Mineral Resources Management” SAGES: Systems Approach for Greener, Eco-efficient, and Sustainable mineral resource management project.